Penghalang Penggunaan Tenaga Solar Dalam Bangunan Perindustrian di Batu Pahat, Johor - Leu, Yuk Yein; Mohamed, Sulzakimin; Omar, Roshartini; Shafii, Haryati (Research in Management of Technology and Business, 2023)
Solar energy is energy that exists in this world for free. In Batu Pahat, Johor receives sunshine throughout the year. Therefore, solar energy technology has high potential in Batu Pahat, Johor. In addition, Batu Pahat, Johor also has many industrial areas. Industrial buildings have used a lot of energy and released gases that have polluted the environment. Therefore, the search for energy to replace traditional energy is done to reduce the use of traditional energy such as fossil fuels. Among them, solar energy is an energy that is suitable for use because the weather and climate in Batu Pahat are suitable for the use of solar energy. Although the strategy in Batu Pahat is suitable for the use of solar energy, the use of solar energy in Batu Pahat is still less than satisfactory, especially in industrial buildings that require a lot of energy. Therefore, the objectice is a study on the barriers to the use of solar energy in industrial buildings in Batu Pahat, Johor and measures to encourage the use of solar energy in industrial buildings in Batu Pahat, Johor. The researcher has used qualitative methods to get data from three engineers that have experience as energy managers in industrial buildings. The data collected are analysed using thematic methods. From the findings of the study, researchers have found that the barriers to the use of solar energy in industrial buildings are categorized into three aspects, namely high cost, security and stability and the profit that will be brought to the owner of the industrial building. This study can be used as a reference and source of information and knowledge for industry players, academic researchers, and students.